Cassava stem wastes as potential feedstock for fuel ethanol production: A basic parameter study. (November 2015) - Wei, Maogui; Zhu, Wanbin; Xie, Guanghui; Lestander, Torbjörn A.; Xiong, Shaojun
Abstract: The cassava stem is found to be one of few crop residues containing starch (up to 42% of dry mass) that may be converted to fuel ethanol. The current study was to evaluate the influence of parameters genotype, growth location and harvest time on cassava stem starch contents and yields as well as consequences in ethanol production (non-cellulosic process), based on 180 samples from a full factorial design experiment (3 varieties × 3 locations × 5 harvest times) in Guangxi, China. The potential utilization of stem starch and soluble sugar that varied 14–42% and 3–12.1% of dry mass, respectively, can correspond to an increase of 26% in ethanol production compared to that produced by roots only. The cassava stem starch content was significantly affected by all three studied parameters and location had the largest effect followed by variety and harvest time, while the stem starch yield was significantly affected by location only. The starch and soluble sugar content were significantly correlated with soil properties, e.g., soil pH and organic carbon, S and P contents. A general and positive correlation was also found between the stem and root starch, suggesting a promising potential of using stem starch without reducing root starch production. Highlights: Cassava stem starch content was up to about 42% DM and yield 2.0 Mg DM ha −1 . Location is the most influential factor followed by variety and harvest time. Stem starch and soluble sugar content were correlated with soil properties. A general and positive correlation was also found between the stem and root starch. Stem starch may increase 24.5% of starch or 26% ethanol products from root today.